Rapid identification of Acinetobacter baumannii using novel specific molecular targets derived from pan-genome analysis and its clinical application - Chen, Shuang; Wang, Huayang; Ju, Chen; Zhang, Pengliang; Ren, YongQiang; Chen, Yaxuan; Yi, Xiaoqi; Zhang, JianYing; Zhang, Shenghang; Xiang, Xinran (Frontiers in Microbiology, 2025)
Acinetobacter baumannii is a pathogen capable of causing severe hospital-acquired infections such as ventilator-associated pneumonia and bacteremia, accounting for over 80% of nosocomial infections. Current nucleic acid tests (NATs) for A. baumannii suffer from limitations in specificity and sensitivity due to reliance on suboptimal targets. Therefore, this study aimed to identify novel, highly specific molecular targets for A. baumannii NATs using pan-genome analysis. A total of 9 specific molecular targets for A. baumannii were screened from 642 genome sequences by pan-genome analysis: outO, ureE, rplY, bioF, menH_3, hemW, paaF_1, smpB and ppaX. These specific species targets have been verified by BLAST and PCR of non-target strains to have 100% specificity for A. baumannii. The specificity of the 9 target genes was verified by PCR, and 3 pairs of different PCR primers were designed for each target gene to determine the best sensitivity of PCR method for each target. Corresponding qPCR detection methods of 9 targets was also established and that of ureE was screened with the lowest detection limit of 10−7 ng/μL. The qPCR method based on the ureE gene can achieve rapid, sensitive and accurate detection of A. baumannii in actual samples with interference from non-target bacteria. After verification of 23 samples, the qPCR method based on the mined target met the requirements in sensitivity, specificity and efficiency, and was consistent with the national verification method. ‌These results confirm that novel pan-genome targets with excellent generalizability among A. baumannii strains enhance detection accuracy in hospital environments, bringing hope for rapid clinical identification, timely interventions, and reduced mortality.